Cumulative Effects of Histology Course on Pathology Curriculum: A Dental Student’s Perspective - Ibrahim Khan, Haseeba Arif, Parkha Afridi, Humaira Khan, Rakhshinda Iram, Shabana Kiran (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The way students perceive and express their thoughts significantly influences their success in academics. The purpose of this study was to investigate how the first-year general histology course influences medical students’ perceptions of pathology in the second year of dental school. The survey assessed students’ perspectives on studying the body, their opinions on their initial year’s histology and subsequent year’s pathology courses, and their sentiments regarding the integration of these classes. Method: It was a cross-sectional study conducted using a questionnaire. A five-point likert scale was used. 250 questionnaires were distributed among the dental students of private and government dental college from 2nd year. Out of 250 questionnaires that were disturbed 220 were responded. Sampling type was convenient sampling. Dental students perspective was the main objective hence target population were 2nd year dental students. Pre- tested questionnaire was utilized. SPSS version 20 was used to analyze the data. Result: The data was collected from second year students of private and government dental colleges. Questionnaire was generated using Goggle Forms. A 30 items, self-administrated questionnaires was used. Out of the 220 students 99 were boys (45%) the rest 121(55%) students were girls. The mean age of the participants was 20.12 years (SD = 0.86). Out of which 165 (75%) students recognizes the importance of histology and pathology course. 57% participants considered that the integration of these two courses will bring about a positive change. The integration of histology and pathology into the curriculum in the first year needs to be evaluated, as demonstrated by our experience for a better understanding of the course. Conclusion: It is important to examine the first-year curriculum’s integration of histology and pathology, and some suitable steps must be taken to improve students’ interest in general histology and histopathology. Keywords: Histology, Pathology, Integration, Dental students, Syllabus.